Effect of Exam Stress of 1-4 Year Student on the Human Body - Aminet Askerovna Pseunok (Journal of Global Pharma Technology, 2019)
The research was performed by the authors to study the effect of exam stress on the respiratory system of 1-4 year students. The experiment was carried out in the longitudinal regime for two years with the participation of the same students. Healthy students participated in the experiment voluntarily. We surveyed 89 1-4 year students, of which were 30 boys and 59 were young females aged 18-22 years. The survey was conducted during the intersessional period and on the day of the exam. To study the functional state of external respiration in the examined students, a pneumotachometric type spirometer with a SPIRO-SPECTR calibration syringe was used. The measurements were carried out from 9 to noon since during this period of the day the studied parameters are the most stable. The experiment took into account gender characteristics. Two age groups were formed: 18-19 years old (1-2 years of education) and 20-22 years old (3-4 years of education). Analysis of the research results showed that in the time course of learning from 1 to 4 years, students' adaptive capacity of the respiratory system increases, resulting in increased efficiency and effectiveness of regulatory mechanisms.Keywords: Longitudinal studies, Psycho-emotional stress, Examination stress, Functionality, Respiratory system.